Acetylation of Abelson interactor 1 at K416 regulates actin cytoskeleton and smooth muscle contraction. Issue 9 (9th August 2021) - Wang, Yinna; Liao, Guoning; Wang, Ruping; Tang, Dale D.
Abstract: Actin cytoskeletal reorganization plays an important role in regulating smooth muscle contraction, which is essential for the modulation of various physiological functions including airway tone. The adapter protein Abi1 (Abelson interactor 1) participates in the control of smooth muscle contraction. The mechanisms by which Abi1 coordinates smooth muscle function are not fully understood. Here, we found that contractile stimulation elicited Abi1 acetylation in human airway smooth muscle (HASM) cells. Mutagenesis analysis identified lysine‐416 (K416) as a major acetylation site. Replacement of K416 with Q (glutamine) enhanced the interaction of Abi1 with neuronal Wiskott‐Aldrich syndrome protein (N‐WASP), an important actin‐regulatory protein. Moreover, the expression of K416Q Abi1 promoted actin polymerization and smooth muscle contraction without affecting myosin light chain phosphorylation at Ser‐19 and vimentin phosphorylation at Ser‐56. Furthermore, p300 is a lysine acetyltransferase that catalyzes acetylation of histone and non‐histone proteins in various cell types. Here, we discovered that a portion of p300 was localized in the cytoplasm of HASM cells. Knockdown of p300 reduced the agonist‐induced Abi1 acetylation in HASM cells and in mouse airway smooth muscle tissues. Smooth muscle conditional knockout of p300 inhibited actin polymerization and the contraction of airway smooth muscle tissues without affecting myosin light chain phosphorylation and vimentin phosphorylation. Together, our results suggest that contractile stimulation induces Abi1 acetylation via p300 in smooth muscle. Acetylation at K416 promotes the coupling of Abi1 with N‐WASP, which facilitates actin polymerization and smooth muscle contraction. This is a novel acetylation‐dependent regulation of the actin cytoskeleton in smooth muscle.